The Educational Turn Rethinking the Scholarship of Teaching and Learning in Higher Education - Coleman, Kathryn; Uzhegova, Dina; Blaher, Bella; Arkoudis, Sophie (Rethinking Higher Education, 2023)
This open access book explores how educational researchers working at the edges of innovations in languages and literacies, leadership, assessment, social and cultural transformation, and pedagogies rethink the educational turn in new sites. It engages with the Scholarship of Teaching and Learning (SoTL) for educational researchers to redefine ways of knowing about learning post-COVID and deepen collective understanding of student learning and teaching for next practices to emerge. This book extends the theoretical and practical aspects of the educational turn across multiple contexts as SoTL. It is grounded in a field of practice and ways of knowing, outlining key intellectual principals, and set against specific examples from research. The chapters reference an understanding of the pedagogical implications of the 'educational turn', utilise a broad range of theory and concepts, and explore potential implications for education and next practices.